Designing leadership and soft skills in educational games: The e-leadership and soft skills educational games design model (ELESS) - de Freitas, Sara; Routledge, H. (Wiley-Blackwell, 2013)
While the field of leadership studies includes a large corpus of literature and studies, the literature and scientific research in the field of e-leadership and soft skills used in learning game environments is at present small in scale. While some training environments such as America’s Army have utilised leadership in a game environment, these environments are just now beginning to be exploited for supporting soft skills and leadership training and education. Towards contributing to this newly emerging field of literature and study, this paper presents a new model, the e-Leadership and Soft Skills Educational Design Model (ELESS) for assessing the use and constructing the effective design of soft skills and leadership skills in multiplayer learning game environments. The paper includes a review of the literature around distributed (shared) leadership models and presents some examples of studies assessing how leadership is being used currently in game environments includes a case study of the Leadership Game (LSG) in order to test the efficacy of the model with reference to a practice example.